2022
DOI: 10.1177/17543371221093189
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of velocity measures and regression methods to predict maximal strength ability in the back-squat using a novel linear position transducer

Abstract: The purpose of this study was to examine the reliability of load-velocity profiles (LVPs) and validity of 1-repetition maximum (1-RM) prediction methods in the back-squat using the novel Vitruve linear position transducer (LPT). Twenty-five men completed a back-squat 1-RM assessment followed by 2 LVP trials using five incremental loads (20%–40%–60%–80%–90% 1-RM). Mean propulsive velocity (MPV), mean velocity (MV) and peak velocity (PV) were measured via a (LPT). Linear and polynomial regression models were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…The Vmaxpro sensor was validated and showed a velocity prediction accuracy of 99% for the deadlift ( 18 ). The minimum detectable difference at loads above 20% 1RM is 0.1 m/s ( 19 ). Hence, we used a load of 40 kg (30% of the maximum included 1RM) and set a maximum 1RM of 130 kg (100% of the maximum included 1RM) as the inclusion criterion for TF.…”
Section: Methodsmentioning
confidence: 99%
“…The Vmaxpro sensor was validated and showed a velocity prediction accuracy of 99% for the deadlift ( 18 ). The minimum detectable difference at loads above 20% 1RM is 0.1 m/s ( 19 ). Hence, we used a load of 40 kg (30% of the maximum included 1RM) and set a maximum 1RM of 130 kg (100% of the maximum included 1RM) as the inclusion criterion for TF.…”
Section: Methodsmentioning
confidence: 99%
“…There is a substantial volume of research indicating that using an LVP calculated from the velocity during submaximal warm-up sets is not a valid method of predicting 1RM. 6,7,19,55 For example, Macarilla et al 19 reported an average overestimation of 38.53 kg and limits of agreement of ±82 kg when comparing directly measured back squat 1RM to back squat 1RM estimated using an LVP, while Hughes et al 56 reported limits of agreement of ±19.65 to ±395.43 kg. The results of the current study align with the previous data, as deadlift 3RM estimated using the LVP did not agree with the directly measured 3RM (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Rest periods were 2 min between warm-up sets. Load-velocity profiles and validity of 1-RM prediction methods in different exercises using the Vitruve linear position transducer have been proven reliable (Kilgallon et al, 2022;Pérez-Castilla et al, 2019).…”
Section: Description Of Strength Training Methods and Velocitiesmentioning
confidence: 97%